Jurnal Akuntansi & Investasi:Pengaruh Profitabilitas, Resiko Keuangan, Nilai Perusahaan, Struktur Kepemilikan dan Dividend Payout Ratio terhadap Perataan Laba - Dika Fajar Pratama (Akuntansi FE UMY, 2012)
This research aims to test empirically the effect of profitability, financial risk, firm value, ownership structure and dividend payout ratio to income smoothing. The sample in this research are 33 manufacture companies that have been listed on the Indonesia Stock Exchange in period of 2006 to 2009.